PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, TINGKAT PEMAHAMAN PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP PEMENUHAN KEWAJIBAN PERPAJAKAN (Studi Empiris Wajib Pajak Badan Pada KPP Madya Pekanbaru) - Putra Yuananda Yogi; Zirman Zirman; Supriono Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of the use of information technology, the level of understanding of taxation and awareness of taxpayers on the fulfillment of tax obligations. The object of this research is the Pekanbaru Intermediate Tax Service Office. The method used in this research is hypothesis testing. The population and sample in this study were corporate taxpayers who were registered at the Pekanbaru Intermediate Tax Service Office. The data source of this research is a questionnaire distributed to 91 corporate taxpayer respondents. The data analysis method used in this research is descriptive statistics and multiple linear regression using thedata processing software program Statistical Product and Service Solution (SPSS) version 25.0 for windows. The results of this study indicate that the use of information technology, level of understanding of taxation and awareness of taxpayers has a significant effect on the fulfillment of tax obligations.Keywords: Fulfillment of Tax Obligations, The Use of Information Technology, Level of Tax Understanding, Taxpayer Awareness